ERP Solutions between Success and Failure - Victoria Stanciu; Andrei Tinca (Journal of Accounting and Management Information Systems (JAMIS), 2013)
The paper aims at emphasizing the significant factors determining IT project success and provides useful insides regarding the factors contributing to the IT projects' failure. The paper presents theoretical considerations and approaches on IT project success and failure field and corroborates these findings with authors' research conclusions retained from an empirical study case on two real ERP implementation projects. The paper emphasizes the advantages brought by the ERP solutions reflected in the business increase and business improved organization and control. The authors focus their attention on the success factors of the project emphasizing the importance of the organization's change culture and the adequate change management process, the full commitment of the management and the need of employees' awareness of change and implication in the project. The authors' research results provide useful insides aiming at increasing the likelihood of IT projects' success. The authors consider that the lessons retained from the past mistakes, can help practitioners to gain the knowledge to avoid them in the new projects. Our research conclusions aim at helping project managers to improve the IT project risk assessment process and practitioners in their risk understanding and action.
Keywords: M15; 650; ERP; software implementation; risk; success factors